Expression, Purification and Characterization of the Hepatitis E Virus Like-Particles in the Pichia pastoris - Gupta, Jyoti; Kaul, Sheetal; Srivastava, Akriti; Kaushik, Neha; Ghosh, Sukanya; Sharma, Chandresh; Batra, Gaurav; Banerjee, Manidipa; Shalimar,; Nayak, Baibaswata; Ranjith-Kumar, C. T.; Surjit, Milan (Frontiers in Microbiology, 2020)
Hepatitis E virus (HEV) is associated with acute hepatitis disease, which may lead to chronic disease in immunocompromised individuals. The disease is particularly severe among pregnant women (20–30% mortality). The only licensed vaccine against HEV, which is available in China, is the E.coli purified recombinant virus-like particles (VLPs) encompassing the 368-660 amino acids (aa) of the viral ORF2 protein. The viral capsid is formed by the ORF2 protein, which harbors three glycosylation sites. Baculo virus expression system has been employed to generate a glycosylated VLP, which encompasses 112-608aa of the ORF2 protein. Here, we sought to produce a recombinant VLP containing 112-608aa of the ORF2 protein in Pichia pastoris (P. pastoris) expression system. The cDNA sequence encoding 112-608 aa of the ORF2 protein was fused with the α- mating factor secretion signal coding sequence (for release of the fusion protein to the culture medium) and cloned into the yeast vector pPICZα. Optimum expression of recombinant protein was obtained at 72 hours induction in 1.5% methanol using inoculum density (A600) of 80 and at pH-3.0 of the culture medium. Identity of the purified protein was confirmed by mass spectrometry analysis. Further studies revealed the glycosylation pattern and VLP nature of the purified protein. Immunization of BALB/c mice with these VLPs induced potent immune response as evidenced by the high ORF2 specific IgG titer and augmented splenocyte proliferation in a dose dependent manner. 112-608aa ORF2 VLPs produced in P. pastoris appears to be a suitable candidate for development of diagnostic and prophylactic reagents against the hepatitis E.